Evidence of Asian Carp Spawning Upstream of a Key Choke Point in the Mississippi River. (4th July 2017) - Larson, James H.; Knights, Brent C.; McCalla, S. Grace; Monroe, Emy; Tuttle-Lau, Maren; Chapman, Duane C.; George, Amy E.; Vallazza, Jon M.; Amberg, Jon
Abstract: Bighead Carp Hypophthalmichthys nobilis, Silver Carp H. molitrix, and Grass Carp Ctenopharyngodon idella (collectively termed "Asian carp") were introduced into North America during the 1960s and 1970s and have become established in the lower Mississippi River basin. Previously published evidence for spawning of these species in the upper Mississippi River has been limited to an area just downstream of Dam 22 (near Saverton, Missouri). In 2013 and 2014, we sampled ichthyoplankton at 18 locations in the upper Mississippi River main stem from Dam 9 through Dam 19 and in four tributaries of the Mississippi River (Des Moines, Skunk, Iowa, and Wisconsin rivers). We identified eggs and larvae by using morphological techniques and then used genetic tools to confirm species identity. The spawning events we observed often included more than one species of Asian carp and in a few cases included eggs that must have been derived from more than one upstream spawning event. The upstream extent of genetically confirmed Grass Carp ichthyoplankton was the Wisconsin River, while Bighead Carp and Silver Carp ichthyoplankton were observed in Pool 16. In all these cases, ichthyoplankton likely drifted downstream for several hours prior to collection. Higher water velocities (and, to a lesser extent, higher temperatures) were associated with an increased likelihood of observing eggs or larvae, although the temperature range we encountered was mostly above 17°C. Several major spawning events were detected in 2013, but no major spawning events were observed in 2014. The area between Dam 15 and Dam 19 appears to be the upstream edge of spawning activity for both Silver Carp and Bighead Carp, suggesting that this area could be a focal point for management efforts designed to limit further upstream movement of these species. Received July 18, 2016; accepted May 4, 2017Published online July 19, 2017